The discovery of angiotensin: a foundational step in the history of hypertension - Milei, José (2021)
More than 80 years ago, in 1939 two independent teams in Buenos Aires and Indianapolis, headed by Eduardo Braun Menendez and Irving H. Page, identified the polypeptide angiotensin related to the pressor effect of renal hypertension. The interest of the argentine team in hypertension began in 1931 during Taquini’s visit to Volhard´s laboratory as a member of the Houssay (Nobel Prize, 1947) group (the other members were Braun Menéndez, Fasciolo, Leloir (Nobel Prize 1970) and Muñoz). Two years thereafter, Goldblatt´s demostrated that partial occlusion of the renal arteries produces hypertension in dogs and Houssay, in 1936 predicted the presence of a humoral mechanism and with Fasciolo demonstrated that the ischemic kidneys released a pressor substance. Later on, Taquini proved that the rise in blood pressure which follows the re-establishment of circulation in kidneys was also produced by the release of a substance: “hypertensin (from the plasma of venous blood of acute ischemic kidneys). Soon after, they proved that it was the result of an enzymatic reaction in which renin was the enzyme and plasma the substrate. At the same time, in May 1939 Page et al postulated that renin activated by plasma becomes vasoactive (“angiotonin”). Page and his group (Kenneth, Kohlstaedt, Helmer and Corcoran) began in 1937, with the purification of renin, studying its renal hemodynamic effects and measuring the vasoconstriction in dog´s tail perfused with Ringer´s solution. Because of a fortuitous arrangement, a sample of renin was left on Page´s desk for several days. When he finally tested it, a surprising sharp increase in arterial pressure was observed. Later on, Page et al acknowledged in 1943 the enzymatic nature of the system and both groups agreed to fuse the two original names into “angiotensin”.